Antagonistic effects of titanium dioxide nanoparticles on cadmium-induced nephrotoxicity and intestinal flora imbalance by reducing its bioavailability in rats - Mansi Luo; Jieling Wang; Jianbin Tan; Jing Wang; Hong Lin; Zhe Liu; Tingting Sun; Yun Liu; Ying Jiang; Hongxia Wang; Kexin Wang; Xuedan Xu; et al. (Ecotoxicology and Environmental Safety)
Titanium dioxide nanoparticles (nTiO2) possess unique physicochemical properties, such as large specific surface area, enabling heavy metals adsorption like Cadmium (Cd), yet the combined risks to the ecosystem and human remain unclear. This 90-day study explored the combined effects of nTiO2 (at a population-relevant dose of 100 mg/kg body weight administered via gavage) and cadmium chloride (CdCl2) (50 mg Cd/L by drinking water) on kidney and gut microbiota of rats. Co-exposure of nTiO2 and Cd significantly reduced the nephrotoxicity induced by Cd, with lower levels of urine biochemical indicators and Cd content, milder histopathological changes and ultrastructural damage. A two-way ANOVA analysis suggested antagonism between nTiO2 and Cd on urinary creatinine (CRE) and Urea. Coincidentally, gut microbiota remained unaffected by nTiO2 but was disrupted by Cd. Co-exposure also partially alleviated the adverse changes, restoring the decreased Beta-diversity and the relative abundance of bacteria to control levels. Furthermore, co-exposure resulted in a 19.2 % decline in the blood Cd concentration and an 8.6 % reduction in kidney, while the Cd content of 24 h feces was 3.6 % higher. These findings suggested antagonistic effects of nTiO2 against Cd-induced nephrotoxicity and intestinal flora disorder in rats. The effects might be attributed to the adsorption of nTiO2 on Cd, which resulted in the reduced Cd intake and distribution, coupled with increased excretion, thereby decreasing the Cd bioavailability. This study provides new evidence for understanding the impacts of nTiO2 and Cd on mammals and will contribute to the further risk assessments of co-exposure to human health and environment safety.